Preparation and characterization of polysulfone-polyurethane membranes for recovery of simulated wastewater from industrial textile processes. Issue 14 (20th June 2022) - Bogoni, N. J.; Schut, C. R.; Merck, J. Z.; Duarte, J.; Menezes, C. M.; Giovanela, M.; Zeni, M. A.; Marangoni, C.; Crespo, J. S.
ABSTRACT: Techniques using membranes for the treatment of wastewaters usually promote higher quality of treated water when compared to other processes. Among them, pervaporation has advantages in terms of selectivity in addition to low working pressure, which can prevent clogging problems. Polysulfone and polyurethane have complementary characteristics and are interesting in the context of membranes for industrial applications. In this sense, the aim of this work was to prepare and characterize polysulfone/polyurethane-based membranes and tested them with a simulated wastewater containing the reactive black dye and sodium chloride by pervaporation. In their manufacture, thermal treatment (at 60°C) and photo-radiation treatment (using ultraviolet light) were also applied. The characterizations were performed using different analytical tools. In general, it was possible to verify that all membranes have a dense layer. The thermal analysis allowed to define that the indicated working temperature is below 50°C. With respect to the simulated wastewater treatment, all membranes reached 100% selectivity. Concerning the saline solution, the mean selectivity was around 98.5%. Moreover, the permeate flow values were within the range presented by commercial membranes ranging from 1.6 to 2.4 kg m −2 h −1 . Although for the photoirradiated membranes the photo-graft reaction has occurred, among all membranes, the blend without any treatment stood out from the others, presenting the highest permeate flow of the simulated wastewater. Finally, the results reveal that these membranes are capable of recovering wastewater from textile processes, in addition to having the potential to remove salts from water through the pervaporation process. Highlights Polysulfone/polyurethane-based membranes were not yet evaluated for wastewater recovery. Modifications in the membrane characteristics promoted variations in the permeate flow. Changes in physical–chemical properties of membrane as a result of a photoinitiation reaction. Removal efficiency achieved was 100% for reactive black dye and 98.5% for sodium chloride. A new way of performing pervaporation on the recovery of aqueous solutions. GRAPHICAL ABSTRACT: UF0001